Low levels of TGF-β1 enhance human umbilical cord-derived mesenchymal stem cell fibronectin production and extend survival time in a rat model of lipopolysaccharide-induced acute lung injury - Dong Li; Qingshen Liu; Lei Qi; Xiaoyu Dai; Huan Liu; Yunshan Wang (2016)
Mesenchymal stem cells (MSCs) are an attractive cellular source for cell‑based therapy, tissue engineering and regenerative medicine. However, the use of MSCs is limited by their low incorporation rate in the graft environment. The majority of cells are lost from the graft within 1 month, due to reduced microenvironment or local inflammation at the graft site. The extracellular matrix (ECM) may assist the survival and expansion of MSCs. The present study aimed to identify an effective approach to increase ECM expression levels by MSCs in order to enhance the therapeutic effect and survival rate of MSCs at the injury site. The concentration‑dependent effect of transforming growth factor (TGF)‑β1 on human umbilical cord (hUC)‑MSC proliferation and expression of ECM genes was investigated. MSCs were successfully isolated, cultured and expanded from hUC. A low concentration of TGF‑β1 (0.1 ng/ml) exhibited the optimal effect on hUC‑MSC proliferation and markedly stimulated the expression of ECM genes, particularly fibronectin (FN). Furthermore, treatment with TGF‑β1 caused no alteration in the immunophenotype and differentiation capacity of MSCs. In vivo experiments in rats demonstrated that intravenous injection of control UC-MSCs or TGF-β1-pre-treated UC-MSCs reduced the severity of lipopolysaccharide-induced lung injury, assessed using histology, measurements of the wet‑dry lung weight ratio, and neutrophil count and protein concentration in bronchoalveolar lavage fluid. However, the short‑term (48 h) therapeutic effects of untreated and TGF‑β1‑pre‑treated UC‑MSCs were similar. The survival of MSCs in damaged lungs, determined by Sry gene expression levels, were significantly increased in MSCs pre‑treated with TGF‑β1. In conclusion, pre‑treatment of MSCs with a low concentration of TGF‑β1 enhanced the expression of ECM components, particularly FN, thus, improving the survival and potential therapeutic benefits of MSCs. Pre‑treatment of MSCs with TGF‑β1 may prolong the effective therapy time and represent an efficient therapeutic approach for tissue repair.